History of Relations of Masonry and Russian Orthodox Church in the Late Eighteenth – Early Twentieth Centuries - Borchuk, S.; Khytrovska, Yu. (Український історичний журнал, 2019)
The purpose of this study is an impartial in-depth analysis of the relations between freemasons and the Russian Orthodox Church from the late 18 to the early 20 century. The research methodology is based on the principles of historicism, comprehensiveness and interdisciplinarity. The author uses a wide range of general scientific (analysis and synthesis, generalization) and specially-historical (critical analysis of sources, retrospective, historical-genetic, problem-chronological) methods. The scientific novelty. The paper is the first attempt to study the relations of Masonry and the Russian Orthodox Church in the late 18 – early 20 centuries. Only some of the aspects of this issue have been reflected in the academic literature. The authors introduces archival documents and fundamental works. Conclusions. The authors concludes that there were difficult relationships between Catholic Church and the Masons. The conflict arose, however, not on the basis of Masonic atheism, because Freemasonry considered religion as an important element of the ideological influence on the peoples, while not giving preference to any doctrine, arguing that all religions are equal, equally transient and imperfect. However, despite the serious differences in the ideologies, in the late 18 – early 19 centuries the Catholic Church and Polish Freemasonry went for a rapprochement for political reasons – to fight for the independence of the Commonwealth. The conflict between the Masons and the Orthodox clergy did not reach such a degree of acuteness that it had in Western European countries between the Catholic Church and the Masonic organization. To a large extent, this was the result of a more tolerant attitude of Orthodoxy to dissidence and the complete administrative dependence of this denomination on the state. Even during the reign of Catherine II, Paul I and especially Alexander I, highranking officials belonged to the Masonic organization. The indulgent attitude of the tsarist government to “Royal Art” ceased when it appeared that this organization was involved in political conspiracies against autocracy and national liberation movements. But, despite the strict measures taken by the imperial authorities against the Masonic organization, the lodges continued to exist, but they functioned more secretly. Freemasonry in the 18–19 centuries did not play a leading role in the public-political life of the Russian Empire, including the Right Bank Ukraine but it significantly influenced it. “Royal Art” apparently prepared society for the acceptance of constitutional and republican ideas, the abolition of serfdom and significantly affected the ideological growth of future generations of both the Russian and Ukrainian intelligentsia. In the early 20 century freemasons in Ukraine were much more active in political respect than in Russia. It is no coincidence that the Ukrainian freemasons put forward the idea to leave the former mystical nonsense and fully concentrate their efforts on the political struggle. Although political Freemasonry destroyed autocracy, it could not overcome its fractional disunity and eventually yielded to more organized and politically far-sighted Bolsheviks. Мета статті – неупереджений глибокий аналіз взаємин «вільних каменярів» із Російською православною церквою наприкінці XVIII – на початку ХХ ст. Методологія дослідження базується на принципах історизму, усебічності та міждисциплінарності. Авторка використовує низку загальнонаукових (аналізу та синтезу, узагальнення) і спеціально-історичних (критичного аналізу джерел, ретроспективний, історико-генетичний, проблемно-хронологічний) методів. Наукова новизна. Стаття становить собою першу спробу дослідження відносин масонів та Російської православної церкви наприкінці XVIII – на початку XX ст. Лише окремі аспекти теми знайшли відображення в науковій літературі. Автори опрацювали й залучили архівні документи та матеріали, а також наукові розвідки та монографії. Висновки. Робиться висновок, що з католицькою церквою в масонів відразу склалися непрості стосунки. Конфлікт виник, однак, не на ґрунті масонського «атеїзму», адже масонство вважало релігію важливим елементом ідеологічного впливу на народ, при цьому не надаючи переваги жодному віровченню, стверджуючи, що всі релігії рівні між собою, однаково минущі й недосконалі. Однак, незважаючи на серйозні розбіжності у ідеології, католицька церква та польське масонство наприкінці XVIII – на початку XIX ст. все ж пішли на зближення з політичних міркувань – для виборювання незалежності Речі Посполитої. Конфлікт між масонами і православним кліром не досяг такої гостроти, якої він набув у країнах Західної Європи між католицькою церквою й масонською організацією. Значною мірою це було наслідком толерантнішого ставлення православ’я до інакодумства та цілковитої адміністративної залежності цієї конфесії від держави. Ще за Катерини II і Павла I та, особливо, за часів правління Олександра I високопосадові особи належали до масонської організації. Поблажливе ставлення уряду до «королівського мистецтва» припинилося, коли стало відомо про причетність цієї організації до політичних змов проти самодержавства та до національно-визвольних рухів. Але, незважаючи на вжиті імперськими властями суворі заходи проти масонської організації, ложі продовжували існувати, проте функціонували ще більш утаємничено. Варто зазначити, що якщо масонство у XVIII–XIX ст. й не відігравало провідної ролі у громадсько-політичному житті Російської імперії, у тому числі Правобережної України, то воно істотно впливало на нього. «Королівське мистецтво» вочевидь підготувало суспільство до сприйняття конституційних і республіканських ідей, до скасування кріпосного права й відчутно позначилося на ідеологічному зростанні майбутніх поколінь російської та української інтеліґенції. Політична активність «вільних каменярів» України на початку ХХ ст. була явно вищою, аніж у тодішній Росії. Не випадково саме українські масони висунули ідею полишити містичні практики та цілковито сконцентрувати свої зусилля на політичній боротьбі. Хоча «політичне масонство» знищило самодержавство, проте не змогло здолати свою фракційну роз’єднаність і зрештою поступилося владними повноваженнями більш організованим та політично далекоглядним більшовикам.